Reading Law: Motivating Digital Natives to ‘Do the Reading’ - Liesel Spencer; Elen Seymour (Legal Education Review)
This special issue comes at a time of expanding scholarship into the impact of contemporary economic and managerial practices on the tertiary sector in Australia. Debates about this subject have been going on over a considerable period of time — beginning, perhaps, with the Dawkins reforms of 1988. However, as the market focus of tertiary education has intensified, workloads have escalated and concerns about changes to governance and impacts on the quality of research, teaching and assessment have become more pervasive. Greater scholarly attention to these issues within law has been triggered in part by conversations which have opened up as a result of Margaret Thornton’s generative book Privatising the Public University: The Case of Law